Analisis Tingkat Literasi Keuangan dan Literasi Perpajakan Pengelola UMKM - Aidicha Berliana Shovie Anggraeny; Rahmat Agus Santoso (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The purpose of this research is to evaluate the level of understanding and skills of Small and Medium Enterprises (SME) managers in Gresik City regarding the financial literacy and taxation. Financial literacy and taxation are important aspects in managing finances and fulfilling tax obligations correctly for SME players. The method used by the researchers was a quantitative approach and the application of sampling techniques including convenience sampling and random sampling. In data collection, the instrument used by the researchers was a questionnaire that distributed to 100 SME respondents representing various business sectors. Based on the data analysis conducted, it was found that the level of financial literacy among SME managers in Gresik City is in the moderate category with an average percentage of 66%. It means that the majority of SME players have a basic understanding of financial concepts relevant to their business. In conclusion, the financial literacy and taxation of SME players in Gresik City are at a moderate level. SME players have basic knowledge of financial literacy and taxation, but there are still lacks of financial management skills and in-depth understanding of tax regulations.